2022
DOI: 10.3390/bios12080596
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Hepatitis B Virus E-Antigen with a Nanopore Sensor Based on Collisional Events Analysis

Abstract: Real-time monitoring, simple operation, and cheaper methods for detecting immunological proteins hold the potential for a solid influence on proteomics and human biology, as they can promote the onset of timely diagnoses and adequate treatment protocols. In this work we present an exploratory study suggesting the applicability of resistive-pulse sensing technology in conjunction with the α-hemolysin (α-HL) protein nanopore, for the detection of the chronic hepatitis B virus (HBV) e-antigen (HBeAg). In this app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
3
1
Order By: Relevance
“…Upon the addition of gp32 molecules to the system, we expected two main changes to happen: (i) a reduction in the ssDNA interaction events caused by a decrease in the DNA concentration due to its binding to the protein, and (ii) the emergence of other types of events such as bumping, due to the excessively large size of the ssDNA-gp32 complexes formed. 61 Contrary to what we expected, we observed that the recorded ionic current uctuations were specic to either the ssDNA molecules or the gp32 proteins (Fig. 2Ab, d and Fig.…”
Section: Design Of the Studycontrasting
confidence: 88%
See 1 more Smart Citation
“…Upon the addition of gp32 molecules to the system, we expected two main changes to happen: (i) a reduction in the ssDNA interaction events caused by a decrease in the DNA concentration due to its binding to the protein, and (ii) the emergence of other types of events such as bumping, due to the excessively large size of the ssDNA-gp32 complexes formed. 61 Contrary to what we expected, we observed that the recorded ionic current uctuations were specic to either the ssDNA molecules or the gp32 proteins (Fig. 2Ab, d and Fig.…”
Section: Design Of the Studycontrasting
confidence: 88%
“…Upon the addition of gp32 molecules to the system, we expected two main changes to happen: (i) a reduction in the ssDNA interaction events caused by a decrease in the DNA concentration due to its binding to the protein, and (ii) the emergence of other types of events such as bumping, due to the excessively large size of the ssDNA–gp32 complexes formed. 61 …”
Section: Resultsmentioning
confidence: 99%
“…Surface charge density, 14,15 ion−ion interactions, 11,16,17 and size effects, 18 all contribute to the behavior of ion transport through the confined nanopore. 19 In the nanopore system, electroosmotic forces, 20 electrophoretic forces, 21 electrostatic interactions, 22 van der Waals interactions, 23 and steric hindrance effect 24 together constitute the energy barriers of biomolecule transport. Biological nanopores act as "standard parts"; i.e., one category of them has the same geometric structure, which can be used to detect proteins or peptides with small masses.…”
Section: Introductionmentioning
confidence: 99%
“…In the nanopore system, electroosmotic forces, electrophoretic forces, electrostatic interactions, van der Waals interactions, and steric hindrance effect together constitute the energy barriers of biomolecule transport. Biological nanopores act as “standard parts”; i.e., one category of them has the same geometric structure, which can be used to detect proteins or peptides with small masses. The dwell time of biomolecules can be prolonged by taking advantage of the steric hindrance effect caused by the unique internal structure of biological nanopores. , Most of the solid-state nanopores have a homogeneous surface charge distribution and significant electroosmotic effects, which can act as a resistance to balance the electroosmotic forces.…”
Section: Introductionmentioning
confidence: 99%